The calcium connection : the little-known enzyme at the root of your cellular health - Broady, Brunde; Lacey, Karen; Wilson, Lyle, (Health practitioner) (Skyhorse Publishing, 2021)
Did you know that one single enzyme impacts your odds of contracting most deadly diseases and health conditions? An enormous body of reputable research into this enzyme has been isolated, ignored, and misunderstood by medical experts. The importance of this enzyme simply cannot be overstated. The Calcium Connection: The Little-Known Enzyme at the Root of Your Cellular Health delivers a clear explanation of this enzyme's function and outlines the steps you can take to gain optimal enzyme health. The accessible, information-packed format teaches you all about Calcium ATPase: how it works, what happens when it goes awry, and easy, practical methods to bring it back into balance and protect it--and your overall health. Whether you're a health enthusiast, environmentalist, parent, or just want to be better informed, this book will help you boost your health now and into the future. Brunde Broady recounts her tireless quest to find a cure for her son Knute's compromised health since being whisked away and kept in ICU after birth. The medical establishment could only help manage his condition, but not diagnose or cure him. Doing her own research and documenting everything Knute ate and his reactions to certain foods, she came across two ubiquitous food additives. Diving deeper, she learned how Calcium ATPase, a fundamental regulator of intercellular calcium, is negatively impacted, not only by these additives, but by a torrent of other inhibitors. Knute's health is a testament to Brunde's discoveries, and The Calcium Connection gives readers a front-row seat to understanding how to maintain optimized cellular health.